2015
DOI: 10.1371/journal.pone.0125083
|View full text |Cite|
|
Sign up to set email alerts
|

Determinants of Health-Related Quality of Life in School-Aged Children: A General Population Study in the Netherlands

Abstract: BackgroundHealth related quality of life is the functional effect of a medical condition and/or its therapy upon a patient, and as such is particularly suitable for describing the general health of children. The objective of this study was to identify and confirm potential determinants of health-related quality of life in children aged 4-11 years in the general population in the Netherlands. Understanding such determinants may provide insights into more targeted public health policy.MethodsAs part of a populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
46
2
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 34 publications
3
46
2
2
Order By: Relevance
“…The Spearman correlation coefficient between nausea and vomiting was 0.50 (p<0.01); the coefficient between nausea and fatigue was 0.32 (p<0.01); the coefficient between vomiting and fatigue was 0.14 (p<0.01). Cohen’s effect sizes ( d ) were calculated by dividing the difference in mean scores among subgroups by largest SD and interpreted as: 0.2≤d<0.5 small difference, 0.5≤d<0.8 moderate difference, d≥0.8 large difference (see S2 Table) [38]. Multivariate linear regression was applied to assess the independent associations between nausea, vomiting, fatigue and scores of physical component summary and mental component summary by establishing a set of models.…”
Section: Methodsmentioning
confidence: 99%
“…The Spearman correlation coefficient between nausea and vomiting was 0.50 (p<0.01); the coefficient between nausea and fatigue was 0.32 (p<0.01); the coefficient between vomiting and fatigue was 0.14 (p<0.01). Cohen’s effect sizes ( d ) were calculated by dividing the difference in mean scores among subgroups by largest SD and interpreted as: 0.2≤d<0.5 small difference, 0.5≤d<0.8 moderate difference, d≥0.8 large difference (see S2 Table) [38]. Multivariate linear regression was applied to assess the independent associations between nausea, vomiting, fatigue and scores of physical component summary and mental component summary by establishing a set of models.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, it is important to inform professionals and parents about the impact of school absence on HRQOL. Both aspects of sports and school absence fit within in the “activities & participation” factors of the International Classification of Functioning, disability and health (ICF) as developed by the World Health Organization (WHO), showing that participation is an important factor influencing HRQOL …”
Section: Discussionmentioning
confidence: 91%
“…A recent study in the United States on predictors of HRQOL in adolescents with CBD also found gender associated with HRQOL . Boys reporting higher HRQOL than girls have been demonstrated in (healthy) populations and partially explain the influence of gender on HRQOL. In addition, as mentioned earlier, the HRQOL of girls with CBD may be affected by heavy menstruations, and it is possible that this has a more immediate detrimental effect on HRQOL than the long‐term effects (eg arthropathy) associated with haemophilia, which may have not yet fully manifested in this population …”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Di Battista et al (2014) found that, in adolescents with traumatic brain damage, depression is a determinant of life quality in these adolescents. In a study by Houben-van Herten et al (2015), they conducted a study to determine life quality determinants about health in children aged 4-11 and they found that socio-economical, demographical, family/environmental factors have a contribution to life quality of children. Kupeli (2009), in the study assessing life quality of children with cancer, found that the disorder influence especially school functionality negatively.…”
Section: Discussionmentioning
confidence: 99%